From Literalism to Liberalism: Judicial Interpretation of Freedom of Information in Malaysia - Ikhsan, Muhammad Izwan; Ku Yusof, Ku Mohd Amir Aizat; Kamaruddin, Saslina; Salleh, Rafidah @ Malissa; Herman, Hershan @ Ray; James Matah, Lenny (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2025)
The essence of democratic society is closely tied to the concept of freedom of information. However, in the Malaysian context, there is currently no specific statute explicitly granting this right to the public. While the Constitution’s Article 10(1) ensures the right to freedom of speech and expression, it does not specifically cover the right to information despite international recognition of such right. This article aims to delve into judicial interpretations to determine whether freedom of information is constitutionally protected in Malaysia. It explores two conflicting approaches to constitutional interpretation, namely the literal and liberal methods, which yield contrasting outcomes. The analysis concludes that there has been a noticeable shift in the judiciary towards a more receptive stance on liberal interpretation in recent years. Nevertheless, the enactment of a federal statute specifically addressing freedom of information is deemed the most effective course of action to safeguard this right in Malaysia.